Peaceful and Anti-Violent Online Habitus: Navigating Indonesian School Social Media in Yogyakarta - Nurwanto, Nurwanto; Amalia, Luky Sandra (Universitas Muhammadiyah Yogyakarta, 2025)
Amid the growing use of digital social media among adolescents and schools, online platforms have increasingly become spaces where cyber-violence, intolerance, and hate speech are circulated. The purpose of this article is to analyse the content of anti-violence and pro-peace posted on social media platforms in five senior high schools in Yogyakarta, Indonesia. Previous studies have focused on violence on social media, whereas this study extends the discussion to peace campaigns. It explores contents and netizens’ comments posted from January to June 2021, during the early COVID-19 pandemic. By using Bourdieu’s notion of habitus, this study examines three social media platforms, namely Facebook, Instagram, and Twitter, owned by each of the five schools, and identifies conversational perspectives on peace and anti-violence referred to as online habitus. NVivo (version 1.3) was used to generate dominant words and phrases from the data. The main words and phrases include school academic achievement, appreciation for students and alumni, religious activities, and extracurricular activities. However, peace-related themes were partly reflected in the school social media platforms. The peace-oriented themes generated from the data include public virtues, institutional values, and personal commitment. These thematic foci suggest that anti-violent habitus has been disseminated to a limited extent. In addition, there were fewer responses from netizens regarding peace promoted through social media. This study suggests that future research should involve more schools and examine greater attention to peace and anti-violence campaigns through digital social media.